Value of 3D echocardiography in the diagnosis of arrhythmogenic right ventricular cardiomyopathy. (3rd September 2022) - Addetia, Karima; Mazzanti, Andrea; Maragna, Riccardo; Monti, Lorenzo; Yamat, Megan; Kukavica, Deni; Pagan, Eleonora; Kishiki, Kanako; Prado, Aldo; Marino, Maira; Bagnardi, Vincenzo; Priori, Silvia; et al.
Abstract: Aims: The 2010 Task Force Criteria (TFC) require that both right ventricular (RV) regional wall-motion abnormalities (WMA) and specific RV size cut-offs be met in order to fulfil one of the major criterion for arrhythmogenic right ventricular cardiomyopathy (ARVC) diagnosis. Currently, 2D echocardiography (2DE) and cardiovascular magnetic resonance imaging (cMRI) are used to determine if these criteria are met. Little is known about the diagnostic value of 3D echocardiography (3DE) in ARVC. The aim of this study was to determine whether a combination of 2DE-3DE is non-inferior to the currently used 2DE-cMRI combination in the diagnosis of patients with ARVC. Methods and results: Thirty-nine individuals (47±15 years) with suspected ARVC underwent evaluation of the RV with cMRI, 2DE, and 3DE. 3DE and cMRI were independently used to obtain RV volumes, ejection fraction (EF) and determine the presence of segmental RV WMA. Studies were blindly classified as meeting criteria for ARVC in accordance with the 2010 TFC. Kappa statistics were used to test the concordance between 2DE–cMRI and 2DE–3DE approaches. Using the 2DE–cMRI approach, 3/39 were not affected, 5/39 possible, 8/39 borderline, and 23/39 definite ARVC. The proposed 2DE–3DE approach yielded 5/39 not affected, 7/39 possible, 8/39 borderline, and 19/39 definite diagnoses. The two approaches were highly concordant (k = 0.71; 95% confidence interval: 0.44–0.84). Although 3DE underestimated RV volumes in comparison with cMRI, interfering, in some instances with the fulfilment of a major criterion, it was able to identify more RV WMA (28/39) than 2DE (11/39), with a detection-rate comparable to cMRI (33/39) highlighting a unique advantage. Conclusion: The combination of 2DE–3DE for ARVC diagnosis is comparable to the conventional 2DE–cMRI approach. 3DE should be performed in all suspected ARVC patients to aide in the detection of WMA. Graphical Abstract: Graphical Abstract